Concerns, attitudes, and practices of orthopaedic surgeons towards management of patients with HIV/AIDS in Nigeria - Obalum, D. C. (Springer-Verlag, 2008)
The increasing number of people living with HIV/AIDS is causing concern among surgeons over risk of occupationally acquired HIV infection. This may influence their attitude to such patients. The purpose of this study was to develop a cross-sectional survey of orthopaedic surgeons to assess their concerns, attitudes, and practices towards management of HIV-positive patients in Nigeria. All respondents were males, 55 (73.3%) of them indicated concern over the risk of occupational acquisition of HIV infection and 37 (49.3%) had examined or operated on at least one HIV/AIDS patient. Sixty (79.9%) were willing to be tested for HIV and 51 (67.9%) were previously tested. Fifty-seven (75.9%) would order preoperative HIV screening of high risk patients, and 67 (89.3%) would operate on HIV-positive patients. Most orthopaedic surgeons in Nigeria would operate on HIV-positive patients.